2010
DOI: 10.1007/s11243-010-9414-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic activity for titanium dioxide by co-modification with copper and iron

Abstract: A copper(II) and iron(III) co-modified titanium dioxide nano material was prepared by a simple sol-gel process using titanium(IV) isopropoxide plus copper(II) and iron(III) nitrates as raw materials. The as-prepared nanocomposites were characterized by X-ray diffraction (XRD), diffuse reflectance spectroscopy and photoluminescence spectra. The XRD results showed that the undoped TiO 2 nanoparticles mainly include anatase phase while the Cu, Fe-codoped TiO 2 nanoparticles showed a mixture of anatase phase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…It is noteworthy that the monometallic photocatalysts displayed the lowest DBT conversion of 18.95 % for Fe and 54.88 % for Cu compared to the bimetallic photocatalysts. This observation is similar to studies reported by Liu et al [24] and Zhang [25], where the photocatalytic activity of Cu-Fe co-doped TiO 2 was higher than that of undoped or singly doped photocatalyst. …”
Section: Photocatalytic Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…It is noteworthy that the monometallic photocatalysts displayed the lowest DBT conversion of 18.95 % for Fe and 54.88 % for Cu compared to the bimetallic photocatalysts. This observation is similar to studies reported by Liu et al [24] and Zhang [25], where the photocatalytic activity of Cu-Fe co-doped TiO 2 was higher than that of undoped or singly doped photocatalyst. …”
Section: Photocatalytic Performancesupporting
confidence: 92%
“…A great deal of research has been conducted using Cu or Fe doped TiO 2 , but co-doped Cu and Fe onto TiO 2 is rarely reported. Liu et al [24] and Zhang [25] degraded organic dye pollutants, Reactive Black 5 (RB 5) and Methyl Orange (MO) in wastewater under UV [24] and visible light [25] radiation, respectively. They showed that co-doped Cu and Fe onto TiO 2 displayed significant enhancement in photodegradation of the organic dye pollutants compared to the un-doped TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The visible light source was a 500-W high-pressure xenon lamp equipped with a UV cutoff filter to completely remove the UV portion of the illumination (k \ 400 nm). UV illumination was provided by a 375-W mercury lamp with two main emission peaks at 185 and 254 nm [18]. After sonication of the suspension for 30 min to achieve the adsorption equilibrium, the lamp was turned on.…”
Section: Synthesismentioning
confidence: 99%
“…Modification of titania by doping using transition metals has often been used to enhance its photocatalytic activity and to extend its absorption wavelength from the UV to visible region [8]. The use of Cu and Ni as bimetallic catalysts supported on different semiconductor materials has been reported as the effective method to improve the efficiency of various reactions like carbon dioxide hydrogenation [9], steam reforming of methane [10], liquid-phase glycerol hydrogenolysis by formic acid over Ni-Cu/Al 2 O 3 catalysts [11], decomposition of methane over Ni-SiO 2 and Ni-Cu-SiO 2 catalysts [12], photocatalytic reduction of nitrate [13], azo dye degradation using Cu-Zn/TiO 2 [8], Ni/TiO 2 [14] and Cu-Fe/TiO 2 [15] for methyl orange degradation, and Cu/TiO 2 for Orange II degradation [16]. …”
Section: Introductionmentioning
confidence: 99%